2018
DOI: 10.1080/02680513.2018.1486185
|View full text |Cite
|
Sign up to set email alerts
|

Learning design in diverse institutional and cultural contexts: suggestions from a participatory workshop with higher education professionals in Africa

Abstract: Learning design approaches, such as those adopted by the Open University, provide a set of tools and resources for purposefullydesigning modules with a focus on student experiences. However, many of the current learning design strategies have been situated within specific institutions in Europe and North America. This means that there are several issues worth considering around if and how established learning design approaches make sense in diverse institutional and cultural contexts. To critically assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In other words, learning design has a fundamental importance on how students learn, and learning analytics approaches can benefit by incorporating learning design proxies into their algorithms and visualisation. As highlighted elsewhere in this journal (Mittelmeier et al, 2018), there is some evidence to support that the OULDI approach can be transformative to other institutions, such as in Africa, and more recently in China.…”
Section: Pedagogically Informed Learning Analyticsmentioning
confidence: 86%
See 2 more Smart Citations
“…In other words, learning design has a fundamental importance on how students learn, and learning analytics approaches can benefit by incorporating learning design proxies into their algorithms and visualisation. As highlighted elsewhere in this journal (Mittelmeier et al, 2018), there is some evidence to support that the OULDI approach can be transformative to other institutions, such as in Africa, and more recently in China.…”
Section: Pedagogically Informed Learning Analyticsmentioning
confidence: 86%
“…Teachers are one of the key stakeholders who will access and interpret learning analytics data, draw conclusions about students' performance, take actions to support students, and improve the design of the curriculum. Distance learning institutions need to empower teachers further by introducing appropriate professional development activities to improve teachers skills in effectively using technology and learning analytics dashboards (Mittelmeier et al, 2018;Rienties, Herodotou, Olney, Schencks, & Boroowa, 2018).…”
Section: Professional Development and Training Of Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Since earlier studies had found that there are disciplinary and contextual differences in the ways that learning designs are viewed and labelled, the project team also evaluated the suitability of the OU learning design tools and approaches for use in an African ODL context (Mittelmeier et al 2018) and sought feedback on what adjustments might be needed. An evaluation of two workshops held at Unisa in April 2018, with around 60 participants in total, showed that while large-scale changes to practice might not be envisaged, academic course designers felt that they would take a more systematic, structured and intentional approach to design or revision of their modules.…”
Section: Learning Design Processes and Toolsmentioning
confidence: 99%
“…In some ways, the final paper for this issue, 'Learning design in diverse institutional and cultural contexts: Suggestions from a participatory workshop with higher education professionals in Africa' by Mittelmeier et al (2018) connect all the themes from this issue together. Mittelmeier et.…”
mentioning
confidence: 99%